2013
DOI: 10.1051/0004-6361/201321752
|View full text |Cite
|
Sign up to set email alerts
|

RCW36: characterizing the outcome of massive star formation

Abstract: Context. Massive stars play a dominant role in the process of clustered star formation, with their feedback into the molecular cloud through ionizing radiation, stellar winds, and outflows. The formation process of massive stars is poorly constrained because of their scarcity, the short formation timescale, and obscuration. By obtaining a census of the newly formed stellar population, the star formation history of the young cluster and the role of the massive stars within it can be unraveled. Aims. We aim to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 70 publications
4
60
0
Order By: Relevance
“…This supports the previous study in Minier et al (2013) showing that, based on the morphology of the regions, the gravitational collapse of these condensations (Fig. 10) was likely to be triggered This is also confirmed by the recent age determination of the different stellar populations done by Ellerbroek et al (2013). Furthermore, the exponent α decreases to a value of 1.54 ± 0.02 in region 1+2+3+4.…”
Section: Vela C/rcw 36supporting
confidence: 91%
“…This supports the previous study in Minier et al (2013) showing that, based on the morphology of the regions, the gravitational collapse of these condensations (Fig. 10) was likely to be triggered This is also confirmed by the recent age determination of the different stellar populations done by Ellerbroek et al (2013). Furthermore, the exponent α decreases to a value of 1.54 ± 0.02 in region 1+2+3+4.…”
Section: Vela C/rcw 36supporting
confidence: 91%
“…Note that Gagné et al (2011) adopted an extinction law with reddening parameter R V = 4.0 for Carina, while Kiminki et al (2015) adopted R V = 3.6 for W3; in reality the reddening parameter can vary even among different stars in the same star-forming region. Ellerbroek et al (2012), (4) e If checked, star was among the 67 selected independently by our procedure for identifying OB candidates among IR SEDs that were counterparts to MYStIX X-ray sources.…”
Section: Sed Fitting Results For Previously-publishedmentioning
confidence: 99%
“…H97 reported that their strength did not vary with A V (or E(B − V)) as seen in other Galactic sightlines. Massive star forming regions are known to exhibit anomalous extinction properties (Dahlstrom et al 2013;Oka et al 2013;Ellerbroek et al 2013a). We will report the DIB behaviour towards sightlines in M17 in a separate paper.…”
Section: From the Total Hydrogen Column Density N(h)mentioning
confidence: 99%
“…The overall conclusion is that the extinction is quite patchy, with substantial variation on a spatial scale of 50 arcsec (corresponding to a geometrical scale of 0.5 pc at the distance of M17), similar as to the findings of H97. A dust disk local to the star, for example, may dominate the line-of-sight extinction towards the sources (see Ellerbroek et al 2013a). Studies of individual sources therefore should not rely on average properties of the region, but should be based on a detailed investigation of the extinction in the line of sight.…”
Section: Age Distribution Of the Massive Pms Population In M17mentioning
confidence: 99%
See 1 more Smart Citation